2020
DOI: 10.15517/am.v31i3.40207
|View full text |Cite
|
Sign up to set email alerts
|

Estado actual de la investigación para el cultivo de guayaba en Colombia

Abstract: Introducción. La guayaba (Psidium guajava L.) es considerada una fruta de importancia comercial en más de sesenta países, la cual se utiliza en la agroindustria y consumo en fresco, debido a sus propiedades nutraceúticas, ya que se considera una fuente importante de vitamina C, mejorando así la salud de los consumidores. Objetivo. Determinar el estado actual de la investigación para el cultivo de la guayaba en Colombia. Desarrollo. El cultivo de guayaba en Colombia presenta rendimiento inadecuado en las difere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…In a high Andean phenological study on the agrometeorological influences on the reproductive phase of plants, Mendoza et al (2017) Morton (1987) 0 -2,000 Grows in a wide range of altitudes Solarte et al (2014) 0 -1,800 Venezuela Hoyos (1989) 0 -1,700 This range favors the distribution Natale et al (2008) 0 -1,500 In frost-free places Paull and Duarte (2012) found that rain is the climatic factor that most promotes this reproductive phase (73.4%), when compared to temperature (19.3%), followed by solar radiation or the photoperiod (3.2%). Salazar et al (2006) reported that guava trees need a water supply of about 1,000 to 2,000 m 3 ha -1 year -1 , but Aguilera-Arango et al (2020), in areas with a bimodal system, annual rainfall of 800 to 1,300 mm that is well-distributed, saw good development and production of the crop. On the other hand, Natale et al (2008) stated that the ideal range of rainfall is 1,000 to 1,600 mm, well-distributed throughout the year, but it should not be less than 600 mm year -1 .…”
Section: Watermentioning
confidence: 99%
See 2 more Smart Citations
“…In a high Andean phenological study on the agrometeorological influences on the reproductive phase of plants, Mendoza et al (2017) Morton (1987) 0 -2,000 Grows in a wide range of altitudes Solarte et al (2014) 0 -1,800 Venezuela Hoyos (1989) 0 -1,700 This range favors the distribution Natale et al (2008) 0 -1,500 In frost-free places Paull and Duarte (2012) found that rain is the climatic factor that most promotes this reproductive phase (73.4%), when compared to temperature (19.3%), followed by solar radiation or the photoperiod (3.2%). Salazar et al (2006) reported that guava trees need a water supply of about 1,000 to 2,000 m 3 ha -1 year -1 , but Aguilera-Arango et al (2020), in areas with a bimodal system, annual rainfall of 800 to 1,300 mm that is well-distributed, saw good development and production of the crop. On the other hand, Natale et al (2008) stated that the ideal range of rainfall is 1,000 to 1,600 mm, well-distributed throughout the year, but it should not be less than 600 mm year -1 .…”
Section: Watermentioning
confidence: 99%
“…The sprouting of the terminal branches that will carry the flowers requires an optimal supply of humidity (Mata and Rodríguez, 2000). These same authors reported that a minimum rainfall of 127 to 178 mm per month is required in Hawaii and that irrigation is applied to advance flowering, which also allows scheduling the harvest (Aguilera-Arango et al, 2020).…”
Section: Watermentioning
confidence: 99%
See 1 more Smart Citation
“…Por su parte en Colombia, los principales departamentos productores de guayaba son Meta (con una producción de 140845 t), Santander (32934 t), Boyacá (44200t), Valle del Cauca (18396 t) y Tolima (10044 t). En el departamento del Meta existen aproximadamente 2500 hectáreas sembradas, lo que representa una oportunidad productiva de desarrollo agroindustrial para la población del Piedemonte llanero y regiones como Lejanías, Granada, Acacías y Villavicencio (Aguilera-Arango et al, 2020).…”
Section: Introductionunclassified